New kind of CD-DCSK chaos shift keying secure communication system - Yong ZHU; Jia-nan WANG; Qun DING (Tongxin xuebao)
As existing chaos keying communication systems had the issues of low data transmission rate and weak system confidentiality,a new kind of chaos shift keying communication system:CD-DCSK(correlation delay-differential chaos shift keying) was presented.At the same time lucubrated and simulated the communication performances of this new system.The theoretical deduction and emulational experimentation analysis verified that CD-DCSK has both merits of high confidentiality of CDSK and low BER of DCSK,and its transmission rate is twice as much as original shift keying schemes.Meanwhile,this new communication scheme perfectly achieved the secrecy transmission of age signal.Therefore,it can be clearly seen that this new system is realizable and has high security.